Judith - Gera, Deborah Levine (Boston : De Gruyter, 2014)
This volume includes a new translation and a detailed verse-by-verse commentary, which touches upon philological, literary, and historical questions. The extensive introduction discusses the work's date, historical background, and original language, biblical and classical influences, and the relation between feminism and theology in the work.
O. 16:21-25 EpilogueIII. BIBLIOGRAPHY; Bibliography; IV. INDICES; Index of Ancient Sources; Index of Names and Subjects; Index of Modern Authors.
"This volume includes a new translation and a detailed verse-by-verse commentary, which touches upon philological, literary, and historical questions. The extensive introduction discusses the work's date, historical background, and original language, biblical and classical influences, and the relation between feminism and theology in the work."--ECIP summary.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 630
Keywords: Judith -- (Biblical figure); Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Judith -- (Biblical figure); Bible; Judith (Biblical figure); RELIGION -- Biblical Studies -- Bible Study Guides; Electronic books; Criticism, interpretation, etc